Determination of Boundary Layer Thickness Around Submarine Hull Using Computational Fluid Dynamics(CFD) - شرارة عمار; نسرين محمد (Latakia University Journal -Engineering Sciences Series, 2023)
The study of the boundary layer around the hull of submarines is regarded as one of the complex studies, because of the difficulty in determining the thickness of this layer and the lack of reference studies in this regard. This study aims to determine the thickness of the maximum boundary layer around the hull of a three-dimensional model of a submarine by designing the appropriate finite element network, and determining the appropriate value of ( y  ) for the model at each of the specified velocity so that it covers the entire field of the boundary layer. This study will be carried out using digital modeling and simulation programs in order to solve the Navier-Stokes equations that describe the motion of fluids, in addition determine the maximum boundary layer for each model and at each velocity that satisfies the equation ( y 1   ) in order to ensure that the first node in the finite element network will be within the field of the boundary layer. This study depends on the relationship between the thickness of the boundary layer and the dimensions of the submarine and the flow velocity. Five different scales of three- dimensional models of the same submarine will be designed 1 1 1 1 1 , , , , 1 2 5 10 100       a variable field of flow velocity will be set including 10 different values of velocity, and then the thickness of the maximum boundary layer for each submarine will be determined to get 50 values of the thickness of the maximum boundary layer around the hull of the five submarines models as a function of the geometric dimensions and flow velocity, using ANSYS-FLUENT and depending on the principle of flow reflection.